2014
DOI: 10.1002/bin.1380
|View full text |Cite
|
Sign up to set email alerts
|

Applied Behavior Analysis in Acquired Brain Injury Rehabilitation: A Meta‐analysis of Single‐case Design Intervention Research

Abstract: The purpose of this meta-analysis was to complete a systematic evidence-based review of published behavioral treatment studies employing single-case designs with both children and adults with acquired brain injury. Peer-reviewed journals were searched using PsycINFO, Medline, and ERIC databases with combinations of terms such as brain injury, behavior disorder, behavior therapy, behavior modification, behavior analysis, and verbal behavior. A total of 112 acquisition and reduction studies met the established i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 31 publications
3
31
0
Order By: Relevance
“…In addition, ancestral searches of recent literature reviews of psychological interventions, including neurobehavioural interventions in brain injury rehabilitation, were also conducted (i.e., Alderman & Wood, 2013;Cattelani, Zettin, & Zoccolotti, 2010;Heinicke & Carr, 2014;Wood & Alderman, 2011;Ylvisaker et al, 2007). The flow of information can be seen in Figure 4, which provides the reasons for excluding records at the different stages; the information about the 28 studies included in the meta-analysis is available in a table in the supplemental online material.…”
Section: Example: Meta-analysis Of Neurobehavioural Interventions To mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, ancestral searches of recent literature reviews of psychological interventions, including neurobehavioural interventions in brain injury rehabilitation, were also conducted (i.e., Alderman & Wood, 2013;Cattelani, Zettin, & Zoccolotti, 2010;Heinicke & Carr, 2014;Wood & Alderman, 2011;Ylvisaker et al, 2007). The flow of information can be seen in Figure 4, which provides the reasons for excluding records at the different stages; the information about the 28 studies included in the meta-analysis is available in a table in the supplemental online material.…”
Section: Example: Meta-analysis Of Neurobehavioural Interventions To mentioning
confidence: 99%
“…Wood and Alderman (2011) offer a narrative review of studies on traumatic brain injury that reported positive results of differential reinforcement (for low rates of responding, for other or incompatible behaviours), both in neurobehavioural units and in non-specialized settings, as well as the effectiveness of response-cost (negative punishment) for people who present cognitive impairment and challenging behaviours. In contrast to these three reviews, Heinicke and Carr (2014) performed a meta-analysis of 112 studies (on various aetiologies, including ABI), reporting higher standardised mean differences for skill acquisition (ranging between 14 and 20) than for behaviour reduction-the main object of the current paper-ranging between 4 and 6 SDs. The values obtained in our review (Table 2) are smaller, but the d-statistic controls for small sample bias and autocorrelation, and MPD and SLC control for baseline trend, whereas the standardised mean difference used by Heinicke and Carr (2014) does neither.…”
Section: Summary Of the Evidence On Neurobehavioural Interventions Inmentioning
confidence: 99%
See 2 more Smart Citations
“…FA if often used in the treatment of intractable or maladaptive behaviors of individuals with limited verbal abilities such as people with severe intellectual disabilities (Delgado-Casas, Navarro, Garcia-Gonzalez-Gordon, & Marchena, 2014;Rooker et al, 2014), acquired brain injury (Heinicke & Carr, 2014), or children and adolescents with autism (Foxx, 2008).…”
Section: Functional Analysismentioning
confidence: 99%